Mn(iii)-Catalyzed cascade cyclization reaction of o-acyl aromatic isocyanides with boronic acids. Issue 9 (29th March 2022) - Liu, Jingya; Li, Lei; Bu, Xiubin; Yuan, Yu; Wang, Xin; Sun, Ran; Zhou, Ming-Dong; Wang, He
Abstract : A Mn(iii )-catalyzed cascade cyclization of  o -acyl aromatic isocyanides with boronic acids was examined to give a series of 3-hydroxyindolenines in single-step. This cascade process involved a transmetalation/nucleophilic addition/intramolecular cyclization sequence. Abstract : A Mn(iii )-catalyzed cascade cyclization of o -acyl aromatic isocyanides with boronic acids was carried out via a single-step route to generate a series of 3-hydroxyindolenines under mild conditions. A plausible mechanism involving a cascade transmetalation, nucleophilic addition and intramolecular cyclization sequence was proposed and confirmed. In addition, the reaction procedure featured simple synthesis, wide substrate scope, and excellent functional group compatibility.